Study on the Growth Kinetics and Morphology of Methane Hydrate Film in a Porous Glass Microfluidic Device - Xingxun Li; Cunning Wang; Qingping Li; Qi Fan; Guangjin Chen; Changyu Sun (Energies, 2021)
Natural gas hydrates are widely considered one of the most promising green resources with large reserves. Most natural gas hydrates exist in deep-sea porous sediments. In order to achieve highly efficient exploration of natural gas hydrates, a fundamental understanding of hydrate growth becomes highly significant. Most hydrate film growth studies have been carried out on the surface of fluid droplets in in an open space, but some experimental visual works have been performed in a confined porous space. In this work, the growth behavior of methane hydrate film on pore interior surfaces was directly visualized and studied by using a transparent high-pressure glass microfluidic chip with a porous structure. The lateral growth kinetics of methane hydrate film was directly measured on the glass pore interior surface. The dimensionless parameter (−∆G/(RT)) presented by the Gibbs free energy change was used for the expression of driving force to explain the dependence of methane hydrate film growth kinetics and morphology on the driving force in confined pores. The thickening growth phenomenon of the methane hydrate film in micropores was also visualized. The results confirm that the film thickening growth process is mainly determined by water molecule diffusion in the methane hydrate film in glass-confined pores. The findings obtained in this work could help to develop a solid understanding on the formation and growth mechanisms of methane hydrate film in a confined porous space.